Analisis pengambilan keputusan terhadap pemilihan portofolio saham terbaik menggunakan metode fuzzy analytical hierarchy process dan fuzzy topsis - Marpaung, Dinda Oktari Putri; Nababan, Esther Sorta Mauli (Jurusan Matematika FMIPA Universitas Jember, 2022)
The proses of decision-making in stock investment considers criteria based on the personal preferences of each investor. In addition, investors also need to analyze fundamental factors that include quantitative and qualitative criteria in which external or internal factors are affecting the company. This is because stocks have a high level of risk, so the selection of a portfolio must be done with the right decision. In making decisions based on many criteria can use fuzzy AHP (analytical hierarchy process) and fuzzy TOPSIS methods. The use of fuzzy logic because it can to cope the subjective assessment result of investor preferences. The fuzzy AHP method is applied to obtain the weights of each criterion which are the factors of stock fundamental analysis. The fuzzy TOPSIS method is applied to determine the ranking of alternatives. Based on the analysis and calculation, the most influential sub criteria is inflation rate and top alternative is the company with the BBNI stock code. Keywords: Decision-making, Fuzzy AHP, Fuzzy TOPSIS MSC2020: 90B50, 91B06, 62C86